Effect of gamma rays and colchicine on morphology, flowering and yield attributes of tuberose var. Bidhan Snigdha - SINDHA, MALLIKA; CHAWLA, S.L.; PATIL, SUDHA; NINAMA, VAIDEHEE; TRIVEDI, SARYU (Journal of Ornamental Horticulture, 2025)
A study was taken up to harness the potential of induced mutations (physical and chemical) to diversify the genetic makeup of tuberose var. Bidhan Snigdha for the creation of novel and improved varieties with enhanced ornamental features. Among different doses of mutagenic treatments, least days to 50% sprouting as well as first flower opening, maximum leaf area and number of spikes per clump were recorded in control while, maximum survival percentage with the application of 1.0 kR gamma rays, 0.09% colchicine and in control. The maximum plant height was recorded in 0.07% colchicine treatment, while number of leaves per plant and spike length were in 0.11% colchicine. Rachis length, number of florets per spike, floret length, number of florets open at a time, spike longevity and weight of bulbs per clump were found maximum when bulbs of tuberose variety Bidhan Snigdha treated with 3.5 kR gamma rays. The maximum flower diameter, number of bulblets per clump and weight of bulblets per clump were recorded with the application of 3.00 kR gamma rays whereas, maximum number of bulbs per clump noted in 0.03% colchicine.